Practice patterns of image guided particle therapy in Europe: A 2016 survey of the European Particle Therapy Network (EPTN). Issue 1 (July 2018) - Bolsi, Alessandra; Peroni, Marta; Amelio, Dante; Dasu, Alexandru; Stock, Markus; Toma-Dasu, Iuliana; Nyström, Petra Witt; Hoffmann, Aswin
Abstract: Background and purpose: Image guidance is critical in achieving accurate and precise radiation delivery in particle therapy, even more than in photon therapy. However, equipment, quality assurance procedures and clinical workflows for image-guided particle therapy (IGPT) may vary substantially between centres due to a lack of standardization. A survey was conducted to evaluate the current practice of IGPT in European particle therapy centres. Material and methods: In 2016, a questionnaire was distributed among 19 particle therapy centres in 12 European countries. The questionnaire consisted of 30 open and 37 closed questions related to image guidance in the general clinical workflow, for moving targets, current research activities and future perspectives of IGPT. Results: All centres completed the questionnaire. The IGPT methods used by the 10 treating centres varied substantially. The 9 non-treating centres were in the process to introduce IGPT. Most centres have developed their own IGPT strategies, being tightly connected to their specific technical implementation and dose delivery methods. Conclusions: Insight into the current clinical practice of IGPT in European particle therapy centres was obtained. A variety in IGPT practices and procedures was confirmed, which underlines the need for harmonisation of practice parameters and consensus guidelines.